Methane adsorption in metal-organic frameworks containing nanographene linkers: a computational study - Bichoutskaia, E.; Suyetin, M.; Bound, M.; Yong, Yan; Schröder, Martin (American Chemical Society, 2014)
Metal-organic framework (MOF) materials are known to be amenable to expansion through elongation of the parent organic linker. For a family of model (3,24)-connected MOFs with the rht topology, in which the central part of organic linker comprises a hexabenzocoronene unit, the effect of the linker type and length on their structural and gas adsorption properties is studied computationally. The obtained results compare favourably with known MOF materials of similar structure and topology. We find that the presence of a flat nanographene-like central core increases the geometric surface area of the frameworks, sustains additional benzene rings, promotes linker elongation and the efficient occupation of the void space by guest molecules. This provides a viable linker modification method with potential for enhancement of uptake for methane and other gas molecules.